Observation of classically 'forbidden' electromagnetic wave propagation and implications for neutrino detection. - Barwick, S. W.; Berg, E. C.; Besson, D. Z.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hanson, J. C.; Klein, S. R.; Kleinfelder, S.; Köpke, L.; Kravchenko, I.; Lahmann, Robert; et al. (Journal of Cosmology and Astroparticle Physics, 2018)
Ongoing experimental efforts in Antarctica seek to detect ultra-high energy neutrinos by measurement of radio-frequency (RF) Askaryan radiation generated by the collision of a neutrino with an ice molecule. An array of RF antennas, deployed either in-ice or in-air, is used to infer the properties of the neutrino. To evaluate their experimental sensitivity, such experiments require a refractive index model for ray tracing radio-wave trajectories from a putative in-ice neutrino interaction point to the receiving antennas; this gives the degree of signal absorption or ray bending from source to receiver. The gradient in the density profile over the upper 200 meters of Antarctic ice, coupled with Fermat's least-time principle, implies ray "bending" and the existence of "forbidden" zones for predominantly horizontal signal propagation at shallow depths. After re-deriving the formulas describing such shadowing, we report on experimental results that, somewhat unexpectedly, demonstrate the existence of electromagnetic wave transport modes from nominally shadowed regions. The fact that this shadow-signal propagation is observed both at South Pole and the Ross Ice Shelf in Antarctica suggests that the effect may be a generic property of polar ice, with potentially important implications for experiments seeking to detect neutrinos.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Cosmic ray experiments; ultra high energy photons and neutrinos